2005
DOI: 10.1186/1471-2350-6-43
|View full text |Cite
|
Sign up to set email alerts
|

The host response to the probiotic Escherichia coli strain Nissle 1917: Specific up-regulation of the proinflammatory chemokine MCP-1

Abstract: Background: The use of live microorganisms to influence positively the course of intestinal disorders such as infectious diarrhea or chronic inflammatory conditions has recently gained increasing interest as a therapeutic alternative. In vitro and in vivo investigations have demonstrated that probiotic-host eukaryotic cell interactions evoke a large number of responses potentially responsible for the effects of probiotics. The aim of this study was to improve our understanding of the E. coli Nissle 1917-host i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
42
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 45 publications
(41 reference statements)
6
42
0
1
Order By: Relevance
“…The activation of the MAPK pathways by Nissle 1917 will contribute to its observed probiotic properties. It is known that Nissle 1917 inhibits gut leakage and promotes barrier function by enhancing tight junctions through increased ZO-1 expression (52) and that ZO-1 expression is ERK dependent (26). Likewise, among probiotic Lactobacillus species, MAPK-dependent signaling has been shown to be important in stimulating epithelial cell tight junctions and heat shock protein production (45,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of the MAPK pathways by Nissle 1917 will contribute to its observed probiotic properties. It is known that Nissle 1917 inhibits gut leakage and promotes barrier function by enhancing tight junctions through increased ZO-1 expression (52) and that ZO-1 expression is ERK dependent (26). Likewise, among probiotic Lactobacillus species, MAPK-dependent signaling has been shown to be important in stimulating epithelial cell tight junctions and heat shock protein production (45,49).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing interest in investigating the immunomodulatory effects of Nissle 1917 and the role of individual microbial components in these processes. It is known that colonization by Nissle 1917 may lead to an alteration of the hosts' cytokine repertoire, with increased levels of inteleukin-10 (IL-10), IL-12, monocyte chemoattractant protein 1 (MCP-1), MIP2␣, and MIP2␤ (10,52), together with increased immunoglobulin A secretion (11), lymphocyte or macrophage activation (10), modulation of CD4 ϩ clonal expansion (46), and stimulation of antimicrobial peptide production by intestinal epithelial cells and tight junction formation (39,62). In addition, Nissle 1917 activates ␥␦T cells, stimulating CXCL8 and IL-6 release but inhibiting tumor necrosis factor alpha (TNF-␣) secretion (18).…”
mentioning
confidence: 99%
“…The clinical relevance of these investigations results (i) from the fact that probiotics have been administered to patients with therapy-related or disease-related immunosuppression and intestinal barrier dysfunction, in some cases resulting in severe side effects (3,25), and (ii) from the fact that recent reports demonstrated the inflammatory potential of E. coli strain Nissle 1917 (6,44). Our results demonstrate that the intestinal microbiota prevents translocation of the probiotic E. coli strain Nissle 1917 even in the presence of a defective adaptive immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that once translocation of bacteria across the intestinal epithelium into internal organs has taken place, the response of the adaptive immune system exacerbates the disease and accelerates mortality. A previous in vitro study of E. coli strain Nissle 1917 revealed proinflammatory traits (44). Therefore, to determine the virulence of E. coli strain Nissle 1917 in GF-raised Rag1 Ϫ/Ϫ mice on a molecular level, we tested isogenic flagellum and LPS mutants of E. coli wild-type strain Nissle 1917.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a growing interest in investigating the immunomodulatory effect of Nissle 1917. Previous studies showed that colonization by Nissle 1917 may lead to an alteration of the hosts' cytokine repertoire (13,49), increased immunoglobulin A secretion (14), lymphocyte or macrophage activation (13), the modulation of CD4 ϩ clonal expansion (47), the stimulation of antimicrobial peptide production by intestinal epithelial cells (39,52,54), and alterations of the pro-and anti-inflammatory balance of local cytokines (49). Recently it has been shown that Nissle 1917 activates ␥␦T cells, stimulating CXCL8 and interleukin-6 (IL-6) release but inhibiting tumor necrosis factor alpha (TNF-␣) secretion (26).…”
mentioning
confidence: 99%